The CEO’s Secret Weapon How Great Leaders and Their Assistants Maximize Productivity and Effectiveness - Jones, Jan. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Many executives don't take full advantage of the assistant who sits right outside their door. This book educates executives about all the ways in which they can streamline and improve the way they work with the help of a great assistant, while teaching them to identify great candidates and maximize the benefits of this special relationship.